Micro‐computed tomography imaging and probabilistic modelling of rock fracture by freeze–thaw. Issue 3 (29th December 2019) - Maji, Vikram; Murton, Julian B.
Abstract: A major problem in studies of rock fracture by frost is the paucity of direct observations in space and time of the initiation and growth of microcracks and their transition to macrocracks. Such observations are essential to understand the location, timing and controls of rock fracture by freeze–thaw. The aim of the present work is to image and elucidate the early stages of rock fracture by applying imaging and statistical methods to a frost‐weathering experiment using intact specimens of a limestone (chalk) and sandstone. First, micro‐computed tomography (μ‐CT) is used to visualize rock fracture in three dimensions over the course of 20 freeze–thaw cycles and to estimate transverse strain using a pixel‐based approach. Second, probabilistic correlation functions are applied to quantify the progressive expansion of the fracture phase and associated damage to rock specimens. The method of μ‐CT is demonstrated for visualizing the growth and coalescence of microcracks and their transition to macrocracks. Fracture proceeded faster and to a greater extent in chalk relative to sandstone, and the macrocracks in chalk were mostly concentric and vertical. Both fracture development and positive transverse strain (dilation) accelerated after cycle 15, suggesting that a threshold has been exceeded, after which macrocracks were evident. Of three probabilistic correlation functions applied to the μ‐CT results, the modified lineal‐path function – which measures the continuous connectivity of the fracture phase in a specific direction – reveals that damage was more extensive in the chalk than the sandstone. It also allows a novel approach to define and quantify three zones of microcracking during freeze–thaw cycling of anisotropic rock: (1) the zone of inherent flaws ; (2) the zone of active microcracking ; and (3) the zone of weak influence during microcracking . The broader significance of this work is that it provides a new approach to investigate mechanistically how frost action damages rock. © 2019 John Wiley & Sons, Ltd. Abstract : The research aims to elucidate early stages of rock fracture by applying micro‐CT imaging and statistical methods to a physical frost‐weathering experiment in rocks. The outcomes proposed a novel approach to define and quantify three zones of microcracking during freeze–thaw cycling of anisotropic rock: (1) the zone of inherent flaws, (2) the zone of active microcracking, and (3) the zone of weak influence during microcracking based on the linear continuity of the fracture phase in various directions.